Examining the Impact of Financial and Non-Financial Criteria Divergence on Bank Profitability Indicators - Daliri, Hamidreza; Ramezani, Aliakbar; Nasl Mosavi, Seyed Hossein; Modanlo Joibary, Alireza (Business, Marketing, and Finance Open, 2025)
The primary objective of this study is to determine the impact of divergence between financial and non-financial criteria on bank profitability indicators. Given the influence of non-financial criteria on financial criteria and, consequently, their effect on profitability indicators, the present study focuses on the concept of divergence between financial and non-financial criteria. It aims to address the theoretical and research gap concerning the divergence between these criteria and its role in bank profitability indicators. This research is classified as an applied study based on its objective. The geographical scope of the study is a state-owned bank, and the statistical sample includes eleven non-financial performance-related criteria and three financial criteria over the period from 2009 to 2022. To test the hypotheses, structural equation modeling was employed using Smart PLS software. The test results indicate that the relationship between divergence (financial and non-financial criteria) and bank profitability indicators is statistically significant.